PENGARUH INSENTIF TERHADAP PRESTASI KERJA KARYAWAN HOTEL AMEERA PEKANBARU - Widhiana Kusuma Wardani; Firdaus Yusrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The success of a company is influenced by the employee's job performance, and in improving employee’s job performance the company provides motivation for employees to work effectively and productively it is by providing incentives. This research is aimed to find out the Influence of incentive towards Hotel Ameera Pekanbaru employees' job performance. The sample of this study was 35 people, taken from all employees who worked for more than one (1) year at Hotel Ameera Pekanbaru. Technique of collecting data of this research used questionnaire. Classical assumptions of the test using normality test, multicolierity test, and heteroscedasticity test. Data analysis technique used in this research was Multiple Linier Regression Analysis, Hypothesis Test, Correlation Coefficient Analysis (R) and Multiple Determination Coefficient (R2). Based on the results of the research, it is known that: There is a significant positive effect of incentives on employees job performance of Hotel Ameera Pekanbaru, indicated by the multiple linier regression analysis Y = 1,232 + 0,414x1 + 0,277x2 + e. F count (37,256)> F tables (3,295) with Significant (0,000) < 0,05. The determination coefficient value (R2) is 70% and the remaining 30% is influenced by other factors not included in this regression model.Key words: Incentives, Job performance